Low‐Cost Counter‐Electrode Materials for Dye‐Sensitized and Perovskite Solar Cells - Li, Guo‐Ran; Gao, Xue‐Ping (Advanced materials (Weinheim), 2020)
It is undoubtable that the use of solar energy will continue to increase. Solar cells that convert solar energy directly to electricity are one of the most convenient and important photoelectric conversion devices. Though silicon‐based solar cells and thin‐film solar cells have been commercialized, developing low‐cost and highly efficient solar cells to meet future needs is still a long‐term challenge. Some emerging solar‐cell types, such as dye‐sensitized and perovskite, are approaching acceptable performance levels, but their costs remain too high. To obtain a higher performance–price ratio, it is necessary to find new low‐cost counter materials to replace conventional precious metal electrodes (Pt, Au, and Ag) in these emerging solar cells. In recent years, the number of counter‐electrode materials available, and their scope for further improvement, has expanded for dye‐sensitized and perovskite solar cells. Generally regular patterns in the intrinsic features and structural design of counter materials for emerging solar cells, in particular from an electrochemical perspective and their effects on cost and efficiency, are explored. It is hoped that this recapitulative analysis will help to make clear what has been achieved and what still remains for the development of cost‐effective counter‐electrode materials in emerging solar cells. Low‐cost counter materials for dye‐sensitized and perovskite solar cells are summarized, with a focus on the regular patterns that appear in their intrinsic features and structural design.